From Passive Victims to Partners in Their Own Reintegration: Civil society’s role in empowering returned Thai fishermen - Rousseau, David (Anti-Trafficking Review, 2018)
Despite the significant international attention to human trafficking in the fishing industry in Southeast Asia, victims continue to experience poor outcomes after their return to Thailand. The Labour Rights Promotion Network (LPN) has assisted many returned fishermen in the difficult journey that begins after their rescue and repatriation. In this paper, we argue that the poor outcomes are the product of systemic failures in the aftercare processes, which are not sufficiently victim-centred and discourage trafficked fishermen’s participation in prosecutions. This is the case in the criminal justice system, where flaws in victim identification and evidence collection can undermine trafficked persons’ rights and make it extremely difficult for them to obtain compensation—a significant factor in their recovery and reintegration. This same cycle of disenfranchisement is pervasive in reintegration services at large in Thailand, many of which are overly paternalistic and neglect survivors’ individual needs and interests. Civil society organisations can remediate these problems by supporting the government in its efforts to strengthen prosecutions and make the criminal justice system more victim-friendly. More broadly, civil society can contribute to a victim-centred approach that places aftercare in a larger perspective—one that extends beyond the purview of the criminal justice system. This paper will examine two emerging models in post-trafficking service provision: Unconditional Cash Transfers (UCTs) and volunteer social networks, which recognise victim empowerment not just as a means towards better law enforcement, but as an end in itself.